Rituximab in the treatment of rheumatoid arthritis. - Taylor, P (2007)
Rheumatoid arthritis is a chronic, disabling condition and the most common form of inflammatory arthritis affecting approximately 1% of the population. The outlook has improved considerably over the last decade with the recognition that better outcomes accompany early and optimal suppression of synovitis. In some patients, this can be achieved with conventional, oral disease-modifying anti-rheumatic drugs. For those with more severe disease, the introduction of biologic therapies targeting the pro-inflammatory cytokine tumor necrosis factor (TNF)-alpha has led to further, significant improvements in outcome. However, in general, these drugs are being used for long-term maintenance therapy and are associated with a very high expense that limits their availability in most healthcare economies. Furthermore, approximately a third of patients fail to achieve clinically significant responses. There is therefore a need for new, effective approaches to therapy, in particular for those patients refractory to TNF blockade. Rituximab, a B cell-depleting antibody, is the first biologic targeting B cells to be approved in the USA and Europe for the treatment of active rheumatoid arthritis in anti-TNF non-responders. This article reviews the background to this therapeutic approach and the encouraging clinical trial data to date indicating that enduring responses can be achieved in a majority of patients after a single treatment cycle comprising two rituximab infusions given 2 weeks apart.